Agrarpolitik und der Pfad der Tugend; Agricultural Policy and the Path of Virtue - Werner Grosskopf (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– In the next five years the efforts of reforming the common agricultural policy need to be reinforced. One reason is the requirement to intensify the international trade with agricultural products, particularly for development policy reasons. Furthermore, a restructuring of the EU-finances concerning the regional and structural development within the framework of the EU-enlargement and a more intensive management of the natural capital is forthcoming. Starting from the three-dimensional target of sustainability the basic principles of the political alignment are discussed and in particular applied on compliance with the TINBERGEN Principle. The arguments against an accelerated liberalization of agricultural production in the EU are evaluated. Concerning the extent of liberalization it is shown, that there must be distinguished between industrialized and developing countries. Moreover, the study points out the importance of the principle of subsidiarity, due to the fact that overcoming the path-dependency can only be achieved by pursuing this principle.
Keywords: 330; EU-Agrarpolitik; Gemeinsame Marktorganisation; Deregulierung; Subsidiarität